Advances in veterinary investigative pathology techniques for porcine tissues - Owens, Jeana Lee (Kansas State University, 2019)
Investigative pathology strives to link knowledge of disease presentation in the whole organism to the cellular and molecular changes caused by that disease. For this thesis I focused on understanding mechanisms of disease in animals that are relevant to disease presentation in humans. Development of novel diagnostics, medications, and treatments depend on animal studies. Due to their anatomical and physiological similarities to humans, pigs are a valuable experimental animal for researching diseases such as influenza. However, pigs are poorly characterized as regards their immune response to infectious diseases, and specifically in regard to influenza viruses. Therefore, to expand available knowledge on pigs as a model for human diseases, I focused on microscopic localization of immune cell markers as well as a marker for a host cell protease with a role in multiple diseases, including influenza. My first objective was to validate a set of antibodies to visualize select porcine lymphocyte subsets and subtypes using immunohistochemistry (IHC) as part of a study to characterize naturally occurring severe combined immunodeficiency (SCID). SCID is a category of inherited disorders caused by various mutations that affect the adaptive immune system. Naturally occurring SCID has been found in pigs and once better characterized, SCID pigs have the potential to be a valuable biomedical research animal. Consequently, I developed IHC protocols for commercial antibodies, anti-CD3, anti-CD4, anti-Pax-5, including duplex protocols, CD3/CD4 and CD3/Pax-5 on formalin-fixed, paraffin-embedded (FFPE) porcine spleen. These IHC protocols can be used in future studies focused on characterization of lymphocyte presence and distribution in naturally occurring SCID in pigs as well as other studies where analysis of lymphocyte distribution in FFPE tissues is of value. My second objective was to characterize the protein and mRNA expression of host cell protease, type II transmembrane protease, serine S1 member 2 (TMPRSS2 and TMPRSS2, respectively), in a diverse set of porcine tissues and compare these expression patterns to those reported in humans and mice. TMPRSS2 competently activates several respiratory viruses, in particular influenza A (IAV). Unlike mice, swine are naturally susceptible to human IAV strains and their responses to infections are clinically similar to those of humans. Consequently, there is a need to characterize the expression of this protease in the pig beyond the extant knowledge, which is limited to its expression in primary cells derived from the lower respiratory tract. IHC and in situ hybridization (ISH) were used to analyze the distribution of TMPRSS2 and TMPRSS2 in a wide variety of tissues. We found that porcine expression of this protease in the respiratory tract mirrored that in humans and that mice differ in their expression from both humans and pigs in the lower respiratory tract, specifically in their pneumocytes. Consequently, the pig may be a better experimental animal choice for studying the role of TMPRSS2 in human influenza and other respiratory viruses. Furthermore, the TMPRSS2 and TMPRSS2 expression results for multiple other porcine tissue types should be of value to infectious disease and cancer research in other body systems. Overall, the goal of this thesis was to expand available knowledge about pigs in support of their use as experimental animals in biomedical research. In the future, these two projects could come together because in multiple tissues TMPRSS2 was expressed in cells that are morphologically consistent with lymphocytes and it has been shown that lymphocytes play a role in IAV infection. When the necessary reagents for the experimental work under consideration are at hand, the pig should be considered as a suitable experimental animal because of the similarities in human and porcine physiological development and disease presentation.
Keywords: Investigative pathology